Proposal of workshops to prevent violence in teenage students and parents - Campos Castillo, Suly (2019)
Change, with respect to how we resolve conflicts at home and school, is necessary in our society. There are limiting beliefs that are part of our culture and prevent male and female adolescents from developing in an environment of mutual respect, with equal opportunities to set out their views and make decisions regardingtheir present and future. While educational institutions are not the only ones who should be concerned about transforming this reality in our society, they are undoubtedly one of the most important spaces to achieve  this. The aim of this proposal is to provide an alternative to contribute from school with the prevention of violence based on the awareness of adolescent students and parents, around their attitudes and behaviors at home and at the school.